Transport Logistics Main Advantages and Disadvantages of Different Types of Transport - Mamatkulova Dildora Nuritdinovna; Ganijonov Akhrorjon Azimjon o‘g‘li (Zien Journals, 2022)
This article provides information on transport logistics, features, main purpose, its functions, tasks, organizational principles of transportation and types of transport.
Keywords: transport; transport logistics; rail; road